Administração aguda de melatonina na performance e recuperação metabólica após esforço exaustivo: uma investigação sobre o metabolismo intermediário - Faria, Vinícius Silva (2021)
Melatonin is an amphiphilic indoleamine, mainly synthesized by the pineal gland. Evidences demonstrates its ergogenic role in long-term aerobic exercise, as well as its modulating role in energy metabolism. Thus, the aim of this study was to investigate the effect of melatonin on exercise tolerance, proteins involved in intermediary metabolism and their energy substrates in rats submitted to exhaustive swimming exercise at an intensity corresponding to maximum aerobic capacity. Sixty-eight Wistar rats were evaluated, divided into 7 groups: control (Ct: n = 10), treated with melatonin and euthanized 1 h (M1: n = 9) or 3 h after the last procedures (M3: n = 9), exercised group and euthanized 1 h (Ex1: n = 10) or 3 h after the time to exhaustion test (tlim) (Ex3: n = 10), treated with melatonin, exercised and euthanized 1 h (ME1: n = 10) or 3 h after the tlim (ME3: n = 10). After adaptation to the liquid environment, the incremental test was performed to determine the intensity of effort corresponding to the maximal individual aerobic capacity. After 48 hours, the animals received vehicle solution or melatonin (10 mg.kg-1) and 30 minutes later they were submitted to tlim. Blood was collected to analyze the concentration of glucose and triglyceride; skeletal muscle tissue (gluteus maximus, gastrocnemius red and white) to quantify the content of glycogen and triglyceride and soleus to quantify GLUT4, FAT CD36 PGC-1α, and NRF-1; liver was collected for quantification of glycogen content. Data were presented as mean ± standard error, submitted to the independent student t test (tlim); One-way analysis of variance (ANOVA) test (lactacidemia and % body mass); Two-way ANOVA (all other analyses) and Newman-Keuls post hoc. A significance level of 5% was established. The results were divided into chapters 1 and 2. In chapter 1, the animals treated with melatonin had higher content of muscle glycogen and GLUT4 when compared to the control (p < 0.05). Furthermore, animals treated with melatonin showed an increase in performance compared to animals treated with vehicle solution (p = 0.01). In the presence of melatonin, there was a significant increase in the glycogen content 3 h after exercise (ME3; p < 0.05), while in the absence of melatonin no difference was demonstrated (Ex3; p > 0.05), possibly due to GLUT4 increase demonstrated by ME1 and ME3 groups (p < 0.05). Regarding the triglyceride content, there was an increase 1 h after exercise in the presence of melatonin (ME1; p < 0.05), while in the absence of administered hormone, this increase occurred only 3 h after exercise (Ex3; p < 0, 05). In chapter 2, the animals treated with melatonin and exercised showed increased expression of PGC-1α and NRF-1 compared to the control (p < 0.05). Regarding the lipid profile, there was a reduction in animals treated with melatonin compared to animals treated with vehicle (p < 0.05). While, for the glycogen content, there was an increase in animals that received melatonin. Thus, the present study demonstrated that the administration of melatonin increased the availability of glycidic substrates and GLUT4 in skeletal muscle tissue and promoted greater tolerance to physical exercise. Furthermore, melatonin accelerated the replacement of energy substrates and increased GLUT4, FAT CD36 and PGC-1α in exercised skeletal muscle, improving the cellular environment for future efforts, at least from a bioenergetic point of view.